Reactive Eccrine Syringofibroadenoma Associated with Neuropathy, Venous Stasis, and Diabetic Foot Ulcer - Thirawut Sirikham; Salinee Rojhirunsakool; Vasanop Vachiramon (Karger Publishers, 2016)
Eccrine syringofibroadenoma (ESFA) is an uncommon benign adnexal neoplasm which derives from cells of the acrosyringium of eccrine sweat glands. The clinical appearance is nonspecific but the histological features are typical. Five clinical subtypes of ESFA exist: (1) solitary ESFA; (2) multiple ESFA associated with ectodermal dysplasia; (3) multiple ESFA without cutaneous features; (4) unilateral linear ESFA (nevoid), and (5) reactive ESFA associated with inflammatory or neoplastic dermatoses. We report the case of a 42-year-old man with long-standing diabetes and neuropathy, presenting with a 4-year history of asymptomatic erythematous plaques on a background of brown hyperpigmentation on the left foot. The clinical presentation and histopathological findings are compatible with reactive ESFA.